2017
DOI: 10.1016/j.ydbio.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cells are long-lived cells whose production is stimulated by skin injury

Abstract: Mechanosensitive Merkel cells are thought to have finite lifespans, but controversy surrounds the frequency of their replacement and which precursor cells maintain the population. We found by embryonic EdU administration that Merkel cells undergo terminal cell division in late embryogenesis and survive long into adulthood. We also found that new Merkel cells are produced infrequently during normal skin homeostasis and that their numbers do not change during natural or induced hair cycles. In contrast, live ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 52 publications
5
38
0
Order By: Relevance
“…Thus, it was suggested that Merkel cells in human skin might be renewed from a population of undifferentiated keratinocytes or common progenitor cells [55]. Labeling experiments in mice have shown that Merkel cells are long-lived cells that are produced very rarely in adult skin under homeostatic conditions [56]. However, upon mild skin injury, increased numbers of Merkel cells were produced, and fate-mapping showed that their differentiation was induced from touch dome keratinocytes [56].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was suggested that Merkel cells in human skin might be renewed from a population of undifferentiated keratinocytes or common progenitor cells [55]. Labeling experiments in mice have shown that Merkel cells are long-lived cells that are produced very rarely in adult skin under homeostatic conditions [56]. However, upon mild skin injury, increased numbers of Merkel cells were produced, and fate-mapping showed that their differentiation was induced from touch dome keratinocytes [56].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, touch domes were reported to undergo a rapid remodelling and the number of Merkel cells per touch dome oscillated within hair cycles until adulthood . On the other hand, other studies showed that embryonic‐derived Merkel cells survived for at least 9 months and the average number of Merkel cells per touch dome remained steady in both natural and induced hair circles . Moreover, it is also possible that changes in number of Merkel cells under normal development and pathological conditions such as skin inflammation might have distinct effects on sensory biology.…”
Section: Merkel Disc In Itchmentioning
confidence: 99%
“…EdU distribution in murine tissues is extensive and incorporation is stable. For example, Merkel cells from mice whose PLOS NEGLECTED TROPICAL DISEASES mothers were injected with EdU during pregnancy remain labelled nine months after birth, suggesting that the analogue is not removed during DNA repair [30][31][32]. Labelling of replicating host cells within a given tissue section can therefore be used as an internal control for EdU tissue penetration to sites of T. cruzi infection.…”
Section: Replication Of Parasite Nuclear Dna Is Not Synchronised Withmentioning
confidence: 99%